Numerical study on spray collapse process of ECN spray G injector under flash boiling conditions. (15th April 2021) - Guo, Hengjie; Nocivelli, Lorenzo; Torelli, Roberto
Highlights: Spray collapse of the ECN Spray G injector was studied under flashing conditions. The flow development of flashing sprays was strongly tied with the fuel properties. With propane, the flow was transonic and a unique shock structure was formed. The underlying physics of the spray collapse process was discussed in detail. Abstract: This work features a numerical study of the spray collapse process that occurs under flash-boiling, gasoline-direct-injection conditions. The Engine Combustion Network's Spray G injector was modeled, and iso-octane, n-hexane, and propane were used as fuels with the goal to investigate fuel property effects. The development of individual jets and jet-to-jet interaction were analyzed to reveal the physical mechanisms of spray collapse. The results agreed qualitatively well with the experimental data of propane available from the literature and the predictions revealed the model's ability to capture the near-nozzle shock structures witnessed in the experiments. Simulations showed that the flow development of flashing sprays was strongly tied with the fuel properties. Specifically, under-expanded jets were not observed with iso-octane due to the fuel's low vapor pressure. In the case of n-hexane, the jets were under-expanded, and a low-pressure core was observed inside the jets due to the flow expansion. With propane, the very strong expansion caused the flow to become transonic and generate a unique shock structure near the nozzle exit. The shock structure revealed the formation of primary shock cells within the jets and secondary shock cells induced by jet-to-jet interaction. Based on the results, the spray collapse under flash boiling conditions was mainly attributed to two effects, i.e., the decrease in pressure at the spray center induced by the low-pressure cores inside and between the jets, and the isolation effect due to the jet-to-jet interaction which contributed to maintain the pressure differential between the spray center and the ambient.